(untitled) (Journal of Management and Social Sciences, 2026)
Social media in Nigeria has become a contested battleground where keyboard warriors actively manipulate and distort public discourse on critical national issues. This study examined how keyboard warriors contest and shape narrative control on social media in Nigeria between 2014 and 2024. Guided by framing theory, this study adopts a qualitative approach, using case studies of publicly available content from Facebook and X (formerly Twitter). Findings reveal that keyboard warriors’ function simultaneously as disruptive forces that amplify polarisation, spread disinformation, and incite ethnic and political tensions, and as strategic communicators who foster civic engagement, demand accountability, and mobilise collective action. Their dual role establishes a central paradox: the same communicative practices that intensify conflict and spread misinformation also enable civic engagement and accountability. The findings extend scholarship on contested online discourse and pinpoint the power struggles that define information flows in contemporary societies Keywords Keyboard warriors, narrative control, cyber conflict, framing theory, digital culture, social media